Life-of-mine optimization for integrated open stope development and production scheduling using a mixed-integer linear programming framework - Appianing, Emmanuel John Andrew; Ben-Awuah, Eugene; Pourrahimian, Yashar (Mining technology (2018), 2023)
Extraction and development sequences must be scheduled strategically in order to maximize the life of mine. The complexities and computational difficulties associated with underground mine planning makes it challenging and open to further research. This paper presents a mathematical programming framework based on mixed-integer linear programming (MILP) formulation for integrated open stope development and production scheduling. Additionally, the MILP model incorporates backfilling, operational levels control, and stope extraction duration control during production scheduling. The MILP model generated a net present value of $244.7 M and determined the capital, ventilation, operational, and ore pass development schedules as well as mining and processing schedules for a gold project with 25 years mine life. A total of 2.48 Mt of material was extracted and processed out of 2.88 Mt mineralized material.